Alternative methods of construction in projects with short turnover time - Clarin, Raymond P. (College of Architecture, University of the Philippines Diliman, 2013)
Green open spaces provide a variety of functions that satisfy human needs : receration, enhancing the quality of life, improving air quality, ground water storage, climate moderation and flood control. Any attempt to monetize these spaces is challenging since these forms will always possess intangible values that are beyond calculation. A considerable amount of studies have been done on open landscape amenities and their price effects on residential properties, but there is hardly any study available on determining amenity values of green open spaces inside shopping malls, mainly due to varying thrusts of private developers and priorities in space planning. Thies paper aims to approximate the amenity values of parks inside malls and evaluate their sustainability, approaching it from the contingent property valuation angle, using hedonic price modeling. Through a case study oa restaurants inside malls (interviews and mapping inventory), it will establish the correlation between restaurant distances to park amenities falling under the categories of zoning, rental rates, volume of foot traffic, food quality and park features. It is hypothesized that the retail ships or restaurants located near the parks have a higher probability of ROI (return on investment) despirte higher rental fees, based on volume of foot traffic generated by this amenity. To validate this assumption, Geographic Information Systems (GIS) is used as a tool in measuring these observations, using Geographically Weighted Regressions (GWR) analysis. Through statistical data software, factor analysis among variables is performed to determine those that are significant, after which these are entered into a regression analysis to corroborate initial assumptions and hypotheses regarding the inverse proportionality between ROI and zoning/ distance and view to park, i.e. the nearer the shops are to the park, the higher the ROI. It is the researcher's hope that, having the parks' economic viability and sustainability established, it will encourage urban planners and mall developers to allocate more generous portions of green open space, thereby contributing to the general welfare of its users and ultimately enhancing the sense of place and communion with nature.